2015
DOI: 10.1586/14779072.2015.1072047
|View full text |Cite
|
Sign up to set email alerts
|

Treatment options for dyslipidemia in chronic kidney disease and for protection from contrast-induced nephropathy

Abstract: Chronic kidney disease (CKD) is highly prevalent worldwide and represents a major cardiovascular risk factor. Dyslipidemia is present in most patients with CKD and further worsens CKD, creating a vicious cycle. The treatment of CKD-related dyslipidemia has been a controversial topic. The use of statins is recommended in all stages of CKD, but it appears to reduce cardiovascular and renal events only in the early CKD stages, up to stage 3. The use of atorvastatin has proven very beneficial; thus, the earliest w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…However, it has been shown in many clinical studies that dyslipidemia treatment reduces the possibility of CIN development. 44,45 In a study, a relationship was found between HDL-C level and the development of CIN. 46 We found a significant relationship between AIP and the development of CIN in our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown in many clinical studies that dyslipidemia treatment reduces the possibility of CIN development. 44,45 In a study, a relationship was found between HDL-C level and the development of CIN. 46 We found a significant relationship between AIP and the development of CIN in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperlipidemia is associated with the progression of chronic renal disease. [27] In vitro studies have demonstrated that interleukin-1β can promote the absorption of low-density lipoprotein (LDL) and inhibit lipid excretion, thus leading to the formation of foam cells and aggravating renal damage. [28] Recent studies have also indicated that increased lipid endocytosis in podocytes from ORG patients leads to proteinuria and glomerular sclerosis.…”
Section: Abnormal Lipid Metabolismmentioning
confidence: 99%
“…Furthermore, deterioration of kidney function may occur after contrast media administration, even in the absence of CI-AKI [2]. Periprocedural statin use, hydration, N-acetylcysteine, and adenosine antagonists have been reported to help prevent CI-AKI after coronary angiography [4][5][6].…”
Section: Letter To the Editormentioning
confidence: 99%